Neutrinos in Particle Physics, Astronomy and Cosmology - Xing, Zhi-Zhong.; Zhou, Shun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
"Neutrinos in Particle Physics, Astronomy and Cosmology" provides a comprehensive and up-to-date introduction to neutrino physics, neutrino astronomy and neutrino cosmology. The intrinsic properties and fundamental interactions of neutrinos are described, as is the phenomenology of lepton flavor mixing, seesaw mechanisms and neutrino oscillations. The cosmic neutrino background, stellar neutrinos, supernova neutrinos and ultrahigh-energy cosmic neutrinos, together with the cosmological matter-antimatter asymmetry and other roles of massive neutrinos in cosmology, are discussed in detail. This book is intended for researchers and graduate students in the fields of particle physics, particle astrophysics and cosmology. Dr. Zhizhong Xing is a professor at the Institute of High Energy Physics, Chinese Academy of Sciences, China; Dr. Shun Zhou is currently a postdoctoral fellow at the Max Planck Institute for Physics, Germany.
Neutrinos: Past, Present and Future -- Neutrinos within the Standard Model -- Neutrinos beyond the Standard Model -- Phenomenology of Neutrino Oscillations -- Neutrinos from Stars -- Neutrinos from Supernovae -- Ultrahigh Energy Cosmic Neutrinos -- Neutrinos and Big Bang Nucleosynthesis -- Neutrinos and Cosmological Perburbations -- Neutrinos and Matter-Antimatter Asymmetry -- Other Topics of Neutrino Astrophysics.
Keywords: Physics; Astronomy; Astrophysics; Cosmology; Nuclear physics; Heavy ions; Hadrons; Physics; Particle and Nuclear Physics; Astronomy, Astrophysics and Cosmology; Nuclear Physics, Heavy Ions, Hadrons; Electronic books